PROBLEMS OF PHYSICAL EDUCATION OF STUDENTS IN TURKISH EDUCATIONAL INSTITUTIONS (LATE 19TH - EARLY 20TH CENTURY) - Khasanov Abdurakhim Khasanovich (Modern American Journals, 2025)
Physical education as a part of the general culture has practical significance. The article deals with the social significance of physical culture and sports in education.
Keywords: Physical education, sports, education, spiritual education, aesthetic education, labor education, recruiting offices.